Synthesis of New Opioid Analgesic Peptide Analogues to Enkephalin (Leucine- and Methionine-Enkephalin) - Muthanna S. Al-Ttaee; Kawkab Y. Saour; Ahlam J. Qasir (College of Pharmacy University of Baghdad, 2017)
A small number of researches were done in the design and synthesis of enkephalin analogues that are able to resist degradation effect of proteolytic enzymes with good bioavailability and half-lives.Through studying structure activity relationships we tried to incorporate phthalyl group, tryptophan and lysine amino acids in different positions in the basic backbone structure of the naturally occurring opioid Leu5- and Met5- enkephalin, in the hope that such insertion of these amino acids could induce interesting addition in the biological activity of these analogues with enhancement of their bioavailability, in addition to decrease side effects as addiction liability. These synthesized peptides are: • Analogue I: phthalyl-tyrosyl-glycel-tryptophan methyl ester. • Analogue II: Boc-tyrosyl-glycyl-phenylalanyl-lysine ethyl ester. HBr. According to the designed structures, the analogues were synthesized following the conventional solution method and they were identified using the following techniques: melting point, optical rotation, thin layer chromatography (TLC), infrared spectroscopy (IR), elemental analysis (CHN) and amino acid analysis. Key words: peptide, phthalyl, opoioid analgesics